Promessas constitucionais e pol??ticas p??blicas: o controle das decis??es pol??ticas no processo de formula????o das pol??ticas p??blicas e o papel do Minist??rio P??blico - Silva Neto, Nathan da (2016)
This study supports the idea that the intervention of the public prosecutor in the public policy process, ie, the steps of creation of public policies, as policy decisions watchdog, is a measure that provides editing policies compliant with the Federal Constitution, ie, quality public policy, efficient, and able to promote the evolution of Brazilian society, always with respect to the constitutional precepts. Initially, the study presents a conceptual notion of public policy, pointing at this point, a behavioral approach to this conceptual notion. Further, we state that the formulation of activity of public policy stems from an eminently political and decision-making, marked, therefore, by an immanent discretion. On the characteristics that mark this formulation process, the study addresses the theories of public choices and limited rationality to demonstrate the need for control of the decisions taken in the public policy process, given the risks arising from the political discretion abuse. The study presents a constitutional notion of discretion to highlight the submission process of developing public policies to constitutional principles. In this discussion, we stress the constitutional principle of efficiency and its close relationship with the Economic Analysis of Law, a connection that increases the demand for great public policy, top quality, considering the resources available. Given the concern to ensure the formulation of appropriate public policies (efficient, high quality) the study concludes that the prosecution, because of its constitutional profile and the legal instruments available to it, can and should manage a set of strengthening relations / punishment to control the decisions of policy makers in order to edit that public policy in accordance with the Federal Constitution.